2. (a) Prove 1 %3D n=0 > na" (1 – x)² n=0 Hint: for the first one, multiply the sum by r and see how it compares to the original. Then take the derivative of that and see how it compares to the second sum. (b) Use this to prove E nhwge -n hun E hwne "EB -n- n=0
2. (a) Prove 1 %3D n=0 > na" (1 – x)² n=0 Hint: for the first one, multiply the sum by r and see how it compares to the original. Then take the derivative of that and see how it compares to the second sum. (b) Use this to prove E nhwge -n hun E hwne "EB -n- n=0
Related questions
Question
![2. (a) Prove
1
%3D
n=0
> na"
(1 – x)²
n=0
Hint: for the first one, multiply the sum by r and see how it compares to the original.
Then take the derivative of that and see how it compares to the second sum.
(b) Use this to prove
E nhwge
-n
hun
E hwne "EB
-n-
n=0](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F5edf3b93-3aff-4c16-90eb-deaa12bfa77c%2F474479c4-16a9-4ed5-b958-9082033c61b3%2Flk7296f_processed.png&w=3840&q=75)
Transcribed Image Text:2. (a) Prove
1
%3D
n=0
> na"
(1 – x)²
n=0
Hint: for the first one, multiply the sum by r and see how it compares to the original.
Then take the derivative of that and see how it compares to the second sum.
(b) Use this to prove
E nhwge
-n
hun
E hwne "EB
-n-
n=0
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
This is a popular solution!
Trending now
This is a popular solution!
Step by step
Solved in 3 steps with 2 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)